TEDE 1. Youth and agriculture messaging the what, when, and how of netizen engagement (2018)
Social memes are increasingly being used to convey messages of key importance to netizens. In this paper, we analyzed the types of interactions generated by 55 memes uploaded in the Infomediary Facebook page. These memes conveyed different messages with youth and agriculture as the central theme. They were posted from February to September 2017. The types of interactions being referred to are the number of likes, comments, reach, and shares generated by these memes. Results show that the post reach range from 1,100 to 4,000. Noticeable and severe fluctuations among these posts were recorded in September in which a meme reached 72,000 users. This meme was on the positive effects and benefits received by farmers through their interaction with the infomediaries in their community. Infomediaries are high school students mobilized to serve as information providers in their respective communities. The top 10 most viewed photos were posted either Wednesday or Friday, consistently at 6PM. The hashtags #RiceAndYoung People and #InfomediaryCampaign were consistent in the top ten posts with the highest number of reach. In terms of the interactivity of users, 11 out of the 55 photos, representing 1/5 of the total number of photos posted from February to September 2017, were commented by Facebook users. Data also show that photos posted during February to March 2017 have the most number of comments. Most of the user's comments express support and agreement with the advocacy of the Infomediary Campaign. This paper also forwards recommendations on how to deal with declining post reach and how to boost youth engagement in social media campaigns targeting climate action and agriculture, in general.